1994
DOI: 10.1063/1.356310
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrical conductivity of zinc oxide thin films by ion implantation of gallium, aluminum, and boron atoms

Abstract: Effect of ion implantation on the conductivity of zinc oxide was examined by using highly resistive zinc oxide thin films deposited by rf magnetron sputtering at room temperature to reduce the effect of oxygen vacancies. With the doping by 1×1017 atoms/cm2 gallium the conductivity is 1.0×103/Ω cm for as-implanted film and it increases up to 3.7×103/Ω cm, the highest conductivity reported for zinc oxide films, with raising the annealing temperature in either a nitrogen or oxygen atmosphere. The conductivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 3 publications
1
31
0
Order By: Relevance
“…On the other hand, Ga-doped zinc oxide (GZO) has been widely studied as a type of low resistivity n-type transparent conducting oxides (TCO) [6,7]. A number of studies have been devoted to improving the electrical conductivity and transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ga-doped zinc oxide (GZO) has been widely studied as a type of low resistivity n-type transparent conducting oxides (TCO) [6,7]. A number of studies have been devoted to improving the electrical conductivity and transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with undoped ZnO, impurity-doped ZnO has low resistivity and good stability. ZnO 10.037 or Al) born, indium aluminum [1][2][3][4]. Most of the works related to ZnO use Al as dopant.…”
Section: Introductionmentioning
confidence: 99%
“…It is presently suggested that B substituted for Zn [30] can be oxidized in an O 2 ambience. Such oxidized B is removed from ZnO as a donor.…”
Section: Resultsmentioning
confidence: 99%
“…Several techniques have already been employed to introduce B into ZnO, such as ion implantation [30], metal-organic chemical vapor deposition [31], [32], atomic layer deposition [33], photo-atomic layer deposition [34], PECVD [35], and radio-frequency (RF) magnetron sputtering [36]. Among these, implantation is a more versatile technique in terms of process simplicity, dosage control, and compatibility with a variety of device structures.…”
Section: Introductionmentioning
confidence: 99%